Effects of Postural Management on Hip Migration in Children With Cerebral Palsy: A Systematic Review. Issue 2 (April 2018) - Gmelig Meyling, Christiaan; Ketelaar, Marjolijn; Kuijper, Marie-Anne; Voorman, Jeanine; Buizer, Annemieke I.
Abstract : Purpose: To review the existing literature on the effects of postural management on hip migration in children with cerebral palsy. Methods: A systematic literature search was performed using 5 databases. Quality of articles was assessed and study designs were appraised according to the American Academy of Cerebral Palsy and Developmental Medicine Systematic Review Method. Results: Eight of 655 identified studies were included, reporting postural management in children with cerebral palsy. Seven of 8 studies reported positive effects on hip migration after postural management interventions. However, level of evidence and quality of the articles were low. Conclusion: The evidence for postural management to prevent or reduce hip migration in children with cerebral palsy is limited by the lack of high-quality studies. Strong recommendations for clinical practice are not possible. Future high-quality research is crucial to improve our understanding of the effects of postural management to prevent hip migration in children with cerebral palsy. Abstract : Supplemental Digital Content is Available in the Text.A systematic review of the existing literature on the effects of postural management on hip migration in children with cerebral palsy.